Keratosis follicularis spinulosa decalvans associated with acne keloidalis nuchae - Ilteris Oguz Topal; Ilknur Mansuroglu Sahin; Betül Berberoglu; Mehmet Ozer (Our Dermatology Online, 2014)
Keratosis follicularis spinulosa decalvans (KFSD) is a keratinization disorder characterized by diffuse follicular hyperkeratosis, progressive cicatricial alopecia, corneal dystrophy, and photophobia. Acne keloidalis nuchae (AKN) is a syndrome of chronic folliculitis that manifests as follicular-based pustules and papules on the occipital region of the scalp, which may eventually lead to cicatricial alopecia. Various diseases such as cutis laksa, deafness, aminoaciduria, mental retardation, and atopy have been reported to be associated with KFSD, but AKN is a rare cutaneous manifestation. Herein, we report the case of a patient with KFSD associated with AKN. He was presented to our clinic with follicular-based pustules and papules that had been progressively advancing for five years that were now manifesting as cicatricial alopecia.